Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Judge Robert Coyle, Faye Coyle, Supervisor Deran Koligian, Fresno County Bar Association President Judy Soley at head table